The Relation Between Self-Confidence and Mathematical Problem Solving Ability on Islamic Junior High School Students - Rifa Mar'ah Sholihah; Harry Dwi Putra; Heris Hendriana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Mathematics is very important in life. The self-confidence that students have will certainly affect the process of learning mathematics. Learning objectives measure students' self-confidence towards mathematical problem-solving abilities.The aim of the study was to analyze the relationship between self-confidence and the ability to solve mathematical problems and analyze students' difficulties in solving problems on the System of Two Variable Linear Equations (SPLDV) material at Madrasah Tsanawiyah. Research using quantitative methods with correlation tests. The research sample was 20 Madrasah Tsanawiyah students. The research instrument consisted of a test to measure mathematical problem solving abilities in the form of 3 essay questions, while the non-test instrument was the self-confidence consisting of 20 statement items. . The learning method used conventionally students are divided into several groups randomly. School books are given as a guide for students in learning.The results showed that there was a very strong relationship (r = 0.83) between self-confidence and the ability to solve mathematical problems. Conclusion  the results of the analysis of students' difficulties were found based on the polya step, especially at the stage of proving that students were not yet able to check the correctness of the solution in the process of working on solving mathematics. It is hoped that future research will use problem solving methods to see how self-confidence increases in the ability to solve mathematical problems.